The Challenge of Quality Management: A Service Marketer’s Perspective - Bansal, Harbhajan (Indian Journal of Marketing, 2004)
Service marketers are fast discovering that quality is a critical but intractable element in their organizations’ success. Quality is critical as it is the fountainhead of competitive advantages because services, in a manner similar to what is happening to tangible products, are becoming commodity-like and apparently, lack brand differentiation and quality. On the other hand, quality is intractable due to complex nature of services. The more complex operating and delivery environment that services present necessitates innovative solutions from service marketers.